Gene co-regulation is highly conserved in the evolution of eukaryotes and prokaryotes - Snel, Berend (Oxford University Press, 2004)
Differences between species have been suggested to largely reside in the network of connections among the genes. Nevertheless, the rate at which these connections evolve has not been properly quantified. Here, we measure the extent to which co-regulation between pairs of genes is conserved over large phylogenetic distances; between two eukaryotes Caenorhabditis elegans and Saccharomyces cerevisiae, and between two prokaryotes Escherichia coli and Bacillus subtilis. We first construct a reliable set of co-regulated genes by combining various functional genomics data from yeast, and subsequently determine conservation of co-regulation in worm from the distribution of co-expression values. For B.subtilis and E.coli, we use known operons and regulons. We find that between 76 and 80% of the co-regulatory connections are conserved between orthologous pairs of genes, which is very high compared with previous estimates and expectations regarding network evolution. We show that in the case of gene duplication after speciation, one of the two inparalogous genes tends to retain its original co-regulatory relationship, while the other loses this link and is presumably free for differentiation or sub-functionalization. The high level of co-regulation conservation implies that reliably predicted functional relationships from functional genomics data in one species can be transferred with high accuracy to another species when that species also harbours the associated genes.